2020
DOI: 10.3390/min10050439
|View full text |Cite
|
Sign up to set email alerts
|

The Seven Sisters Hydrothermal System: First Record of Shallow Hybrid Mineralization Hosted in Mafic Volcaniclasts on the Arctic Mid-Ocean Ridge

Abstract: We document the discovery of an active, shallow, seafloor hydrothermal system (known as the Seven Sisters Vent Field) hosted in mafic volcaniclasts at a mid-ocean ridge setting. The vent field is located at the southern part of the Arctic mid-ocean ridge where it lies on top of a flat-topped volcano at ~130 m depth. Up to 200 °C phase-separating fluids vent from summit depressions in the volcano, and from pinnacle-like edifices on top of large hydrothermal mounds. The hydrothermal mineralization at Seven Siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…Since the hydrothermal vents took into analysis in this study were only the ones found below 200 meters depth, in case we found updated depth record of fields or sites, we changed the dataset accordingly. For example, the field named Seven Sisters was removed after finding new reference of its depth at 130 m 90 .…”
Section: Active Hydrothermal Ventsmentioning
confidence: 99%
“…Since the hydrothermal vents took into analysis in this study were only the ones found below 200 meters depth, in case we found updated depth record of fields or sites, we changed the dataset accordingly. For example, the field named Seven Sisters was removed after finding new reference of its depth at 130 m 90 .…”
Section: Active Hydrothermal Ventsmentioning
confidence: 99%
“…Several high-temperature hydrothermal vent fields are located on the AMOR (Pedersen et al, 2010b;Pedersen and Bjerkgård, 2016), of which we focus on three in this study: Seven Sisters, Jan Mayen and Loki's Castle (Table 1). Seven Sisters is a shallow hydrothermal vent field (120 m depth) that occurs in mafic volcaniclastic rocks on top of a flat-topped volcano on the Kolbeinsey Ridge (Marques et al, 2020). Fluids of up to 200°C vent from barite and anhydrite-rich structures and are low in metals, CH 4 and H 2 (Marques et al, 2020) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Seven Sisters is a shallow hydrothermal vent field (120 m depth) that occurs in mafic volcaniclastic rocks on top of a flat-topped volcano on the Kolbeinsey Ridge (Marques et al, 2020). Fluids of up to 200°C vent from barite and anhydrite-rich structures and are low in metals, CH 4 and H 2 (Marques et al, 2020) (Table 1). The Jan Mayen vent fields are situated on the southern Mohns Ridge at a depth of 550-700 meters (Pedersen et al, 2005), and consist of the Troll Wall, Soria Moria and Perle & Bruse venting areas.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report the first study of a temperate phage infecting H. thermotrophus: a free-living, Gram-negative, moderately thermophilic bacterium isolated from a microbial mat collected from the Seven Sisters hydrothermal vent field located on the Arctic Mid-Ocean Ridge [ 55 , 56 ]. Within the phylum Fusobacteria, Hypnocyclicus thermotrophus IR-2 T (=DSM 100055 =JCM 30901) is listed as the current type strain of the genus Hypnocyclicus .…”
Section: Introductionmentioning
confidence: 99%